(untitled) (World Economics and Finance Bulletin, 2025)
Takaful, a form of Islamic insurance grounded in the principles of mutual assistance and ethical finance, offers an alternative model to conventional insurance. This paper explores the opportunities for integrating takaful into Uzbekistan’s insurance sector, highlighting its relevance in the local socioeconomic and religious context. Drawing upon international practices and established takaful models, including Wakalah, Mudarabah, and hybrid structures, the article assesses the prospects for implementing this system in Uzbekistan. It also identifies existing barriers and suggests strategic steps for successful adaptation and institutional support within the national financial framework